The Impact of Difference of Opinions and the Google Search Volume Index on the Phenomenon of IPO Underpricing - Astari, Ni Putu Erviani; Puspitha, Made Yessi (Journal of Business and Management Review, 2025)
Research Aims: The purpose of this study is to ascertain how the Google Search Volume Index and difference of opinions affect the Indonesia Stock Exchange's IPO underpricing phenomenon. Design/methodology/approach: With secondary data, this study uses quantitative methodologies. Purposive sampling is the approach used for sampling, and 416 research samples are included in total. Multiple linear regression analysis is the method utilized for data analysis. Research Findings: This study demonstrates that difference of opinions has a negative effect on the underpricing phenomenon during initial public offers (IPOs). Investor interest has a favourable effect on the underpricing phenomenon during initial public offerings (IPOs). This shows that even when investors look for additional information about a company's shares on the Internet, they are still interested in information about initial price changes. As a result, investors' focus is drawn to the underpricing of public offerings (IPOs), which leads to a difference of opinions on the IPO's value. Theoretical Contribution/Originality: This study provides an understanding of the influence of the Google Search Volume Index and Differences of Opinion on the Phenomenon of IPO underpricing on the Indonesia Stock Exchange. These findings provide valuable insights for investors and companies seeking to optimize their investment and funding policies.